Status of irrigated area in the Limpopo River Basin: June 2024 - Kiala, Zolo; Matheswaran, Karthikeyan (International Water Management Institute, 2024)
In June 2024, the Limpopo River Basin (LRB) area under irrigated agriculture was mapped using a machine learning approach within Google Earth Engine (GEE).